Kinship w ujęciu posthumanistycznym. Międzygatunkowe rodziny przyszłości - Gajewska, Grażyna (Przestrzenie Teorii, 2023)
The author analyzes the works of Patricia Piccinini (sculpture), Shaun Tan (literature) and Joon-ho Bong (film) in terms of the post-humanist idea of interspecies familiarity. The text begins with an explanation of the term Kinship, and then indicates to what extent post-humanism extends its scope and describes the emotional ties between human and other-than-human members of the household. The author presents this kind of post-humanist, multi-genre family life in three different versions: in the field of visual arts, these will be works from the Welcome Guest, and Families of the Future by Piccinini, in the field of the literature – Tan’s Tales from the Inner City, and the film representation – Okja by Bong. Although each of these works brings out slightly different aspects and contexts of the post-humanist vision of the concept of Kinship, they share an openness to what is other-than-human, combined with care and tenderness.